Influence of unconventional monetary policy on agricultural commodities futures: network connectedness and dynamic spillovers of returns and volatility. Issue 22 (9th May 2023) - Umar, Zaghum; Sayed, Ayesha; Gubareva, Mariya; Vo, Xuan Vinh
ABSTRACT: Our research examines connectedness landscape and the dynamic spillovers of volatility and returns in the network comprising eleven agricultural commodities and US shadow short rate in a quality of inflation indicator, observed in monetary policymaking. We use daily data from November 2000 to May 2021. We document monetary policy as a net transmitter of spillover for both return and volatility of agricultural commodities. We find significant volatility connectedness among agricultural commodities. The connectedness is shown to be of a time-varying nature, exhibiting considerable increases during periods of market turmoil. The results of this paper provide relevant insights into the interrelations of US monetary policy and agricultural commodity prices, being, hence, potentially useful for commodity investors, brokers and dealers, as well as for market regulators designing policy solutions for financial stability enhancements.